A sturgeon-derived bioactive compound beneficially modulates nuclear receptors controlling metabolic functions in patients with metabolic syndrome - Marotta, Francesco; Lorenzetti, Aldo; Catanzaro, Roberto; Zerbinati, Nicola; Jain, Shalini; Solimene, Umberto; Yaduvanshi, Santos K.; Yadav, Hariom; Sapienza, Chiara; Srivastava, Nalini; Milazzo, Michele; Italia, Angelo (Acta Biomedica Atenei Parmensis, 2013)
The aim of the present study was to test the possible effects of a novel sturgeon-derived compound  (LD-1227) on inflammatory markers related to metabolic nuclear receptors in patients with metabolic syndrome. The study population consisted of 76 patients with metabolic syndrome and 30 healthy subjects who were maintained to their current treatments and randomly supplemented: A) LD-1227 (n=38) or B) placebo (n=38) as compared to C) healthy controls (n=30). LD-1227 or placebo (water-soluble starch) were given daily at breakfast and dinner for three months. Levels of hs-CRP, IL-6, TNF-α, leptin and adiponectin/ resistin index were assayed at the entry, 1 month and 3 months afterwards. At the end of the study period, as compared to B group, LD-1227-treated patients showed a significant improvement of all parameters tested, irrespective of the presence of diabetes. In particular, levels of adiponectin and adiponectin/ resistin index significantly increased following LD-1227 administration. Although the metabolic syndrome remains a multifaceted condition requiring a complex approach, LD-1227 could be a potential safe therapeutic tool to be integrated into a wider treatment and preventive medicine schedule strategy.